Superconductors of the BPSCCO system obtained from rapid cooling process - Carvalho, C. L.; Yukimitu, K.; Reynoso, VCS; Moraes, João Carlos Silos [UNESP]; Araujo, E. B.; Alves, Neri [UNESP]; Rainho, S. (Springer, 2005)
Bi-based (BPSCCO) superconductors have been extensively studied due to their interesting superconducting properties, especially those that present high transition temperature (T-c). In this work, superconductors of the BPSCCO system were prepared from rapid cooling process and studied under its structural and magnetic properties. Sample as-prepared shows an amorphous behavior, which is converted progressively into 2223 phase. This process permits the control of Pb or Bi loss and the crystallization of the desired phase using several heat annealing processes. The 2201 and 2212 phases were also observed as intermediate phases, before the crystallization of the 2223 phase. The superconductor obtained in this work presented a T-c around 77-K. (C) 2005 Springer Science + Business Media, Inc.